(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Ketoconazole is an antifungal medication used to treat a variety of fungal infections. Recent studies suggest that ketoconazole is capable of forming invasomes, which are small vesicles that contain the drug and facilitate its uptake into cells. Invasomes are formed when ketoconazole binds to a membrane receptor, allowing the drug to invade the cell and exert its therapeutic effect. This process is thought to be essential for the efficient delivery of ketoconazole to the affected cells. Invasomes have been found to have a wide variety of applications, such as the delivery of drugs, nutrients, and therapeutic agents. Furthermore, invasomes can be used to target specific tissues or cell types, allowing for the delivery of drugs to specific areas of the body. The formation of invasomes by ketoconazole is a promising avenue for the treatment of fungal infections, as it can provide a more efficient and targeted delivery of the drug. The results from the study of the invasomes of ketoconazole show that the drug is able to penetrate the bacterial cell membrane and form an invasome. This method of delivery allows for greater targeted release of the drug, increased stability, and improved bioavailability. Further studies are needed to determine the efficacy and safety of this new delivery system. The formulation of ketokonazole invasomes is a promising new method for treating fungal infections. This method has the potential to provide higher levels of drug delivery, increased bioavailability, and improved efficacy. Further research is needed to evaluate the safety and efficacy of ketokonazole invasomes in humans.